2014
DOI: 10.1021/ic501939k
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Characterization, Electronic Band Structure, and Thermoelectric Properties of the Cluster Compound Ag2Tl2Mo9Se11

Abstract: We report on a detailed investigation of the crystal and electronic band structures and of the transport and thermodynamic properties of the Mo-based cluster compound Ag2Tl2Mo9Se11. This novel structure type crystallizes in the trigonal space group R3̅c and is built of a three-dimensional network of interconnected Mo9Se11 units. Single-crystal X-ray diffraction indicates that the Ag and Tl atoms are distributed in the voids of the cluster framework, both of which show unusually large anisotropic thermal ellips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 58 publications
(119 reference statements)
6
38
0
Order By: Relevance
“…Most of the recently-discovered families of thermoelectric materials reach their maximum ZT values at high temperatures, typically between 700 and 1200 K [4][5][6][7][8][9][10][11][12]. For thermoelectric applications near room temperature, solid solutions of bismuth telluride Bi 2 Te 3 with the isomorphous compounds Sb 2 Te 3 and Bi 2 Se 3 are still nowadays the best materials with ZT values around unity in both pand n-type compounds [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the recently-discovered families of thermoelectric materials reach their maximum ZT values at high temperatures, typically between 700 and 1200 K [4][5][6][7][8][9][10][11][12]. For thermoelectric applications near room temperature, solid solutions of bismuth telluride Bi 2 Te 3 with the isomorphous compounds Sb 2 Te 3 and Bi 2 Se 3 are still nowadays the best materials with ZT values around unity in both pand n-type compounds [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter research, several families of semiconductors have been identified in recent years, all with very low thermal conductivity whose temperaturedependence mimics that of amorphous alloys. Among others, these include Zintl phases, 1,2 Mobased cluster compounds, [3][4][5] chalcogenide-based compounds, [6][7][8] and such cage-like structures as clathrates. 9,10 Combined with semiconductor-like properties, the extremely low thermal conductivity results in high dimensionless thermoelectric figures of merit, ZT, defined as ZT = S 2 /(qj)T where T is the absolute temperature, S the Seebeck coefficient or thermopower, q the electrical resistivity, and j the total thermal conductivity, which is the sum of a lattice contribution j l and an electronic contribution j e .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the underlying physical mechanisms responsible for the glass-like thermal conductivity (κ) exhibited by some crystalline materials has attracted considerable attention over the last few decades for both fundamental and practical reasons. Such unusual behavior has been observed in natural minerals, [1][2][3][4] complex crystal structures with a large number of atoms per unit cell, [5][6][7][8][9][10][11][12] and cage-like compounds, [13][14][15][16][17][18][19][20][21] with the type-I clathrates being one of the most prominent examples. 22 The crystal structure of these materials is composed of covalently bonded frameworks in the large cavities of which "guest" atoms reside [polyhedral cages; Fig.…”
Section: Introductionmentioning
confidence: 82%